2016
DOI: 10.1016/j.fuel.2016.04.125
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/mixed metal oxide hybrid materials for enhanced adsorption desulfurization of liquid hydrocarbon fuels

Abstract: HIGHLIGHTS The adsorption of sulfur from liquid hydrocarbons using mixed metal oxides unsupported and supported on graphene oxide was studied for the first time  Sulfur adsorption capacity and thermal stability of mixed metal oxides is enhanced by the presence of graphene oxide  The GO supported adsorbents show good selectivity for organosulfur compounds over sulfur-free aromatic hydrocarbons KEYWORDSGraphene oxide, mixed metal oxide, dibenzothiophene, adsorption, desulfurization ABSTRACTA series of mixed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Aerwards, a vast amount of literature reported on MOFs as extraordinary adsorbent candidates for ADS. 17,18 Moreover, the adsorption properties can be further improved by integrating carbon materials 8,[19][20][21][22][23] or metal nanoparticles. [24][25][26][27] Petit et al 28 successfully synthesized a novel MOFgraphite oxide (GO) composite structure and found the synergistic effect between MOF-5 and GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Aerwards, a vast amount of literature reported on MOFs as extraordinary adsorbent candidates for ADS. 17,18 Moreover, the adsorption properties can be further improved by integrating carbon materials 8,[19][20][21][22][23] or metal nanoparticles. [24][25][26][27] Petit et al 28 successfully synthesized a novel MOFgraphite oxide (GO) composite structure and found the synergistic effect between MOF-5 and GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that graphene oxide or graphite oxide, despite the presence of acidic functional groups, exhibits low adsorption capacity towards sulfur compounds [24][25][26][27][28]. is can be due to various reasons, such as the disruption of the hexagonal ring structure by the presence of functional groups, the inadequate degree of oxidation which leads to insufficient functional groups, and the inability to control the type of functional groups, or because of low Journal of Nanotechnology speci c surface area due to inadequate exfoliation of the layers [24][25][26][27][28]. However, di erent strategies can lead to the development of adsorbents with high adsorption capacity, by taking advantage of the intrinsic properties of graphene and graphene oxide.…”
Section: Graphene Applicationsmentioning
confidence: 99%
“…However, di erent strategies can lead to the development of adsorbents with high adsorption capacity, by taking advantage of the intrinsic properties of graphene and graphene oxide. ese strategies consist of using graphene or graphene oxide as a support for di erent adsorbents, such as metal oxides [24,25,[27][28][29] or metal-organic frameworks (MOF) [26,30,31]; this synergy can boost their adsorption capacity. Song et al investigated the adsorption capacity of reduced graphene oxide/zinc oxide composites (rGO/ZnO) towards H 2 S [24].…”
Section: Graphene Applicationsmentioning
confidence: 99%
“…Carbon materials including activated carbons, carbon nanotubes, graphene or graphene oxide (GO) have recently drawn increasing attention in various application areas due to their excellent properties and low cost . Early research mainly focused on the excellent adsorption abilities of carbon materials for sulfur‐containing compounds in oil . With further research and better understanding of carbon materials, researchers have found that certain carbon materials exhibited an improved adsorption capacity for ODS products such as sulfones or sulfoxides.…”
Section: Introductionmentioning
confidence: 99%